EFFICACY AND SAFETY OF VASOACTIVE BETA-BLOCKERS IN ACUTE PHARMACOLOGICAL TEST IN HYPERTENSIVE PATIENTS OF DIFFERENT AGES - O. V. Fedorishina; A. A. Dzizinsky; K. V. Protasov; V. A. Protasova; T. I. Kucherova; E. G. Zakharova; D. D. Baskhaeva; T. S. Sukhoroslova; O. V. Perkova (Столичная издательская компания, 2016)
Aim. To evaluate a short-term efficacy and safety of nebivolol and carvedilol in hypertensive patients of different ages in acute pharmacological test (APT).Material and methods. 119 patients with arterial hypertension (HT) 2-3 degrees aged 33-89 y.o. were involved into the study. Patients were split into 2 groups according to age: young and middle-aged patients (30-59 y.o.); elderly and senile patients (≥60 y.o.). All patients were randomized for carvedilol (12.5 mg once daily) or nebivolol (5 mg once daily) therapy after wash-out period (3-10 days). Ambulatory blood pressure monitoring (ABPM) was performed one day before and one day after first drug taking and ABPM indices were compared.Results. APT with carvedilol and nebivolol in patients of young and middle age showed significant antihypertensive effect on systolic (-6.9 and -6.0 mm Hg, resp.), diastolic (- 4.6 and -4.7 mm Hg, resp.) and pulse (-1.7 and -1.4 mm Hg, resp.) blood pressure (BP). In patients of elderly and senile age the first daily dose of nebivolol did not have influence on systolic and pulse BP (-2.73 and +0.50 mm Hg, resp., p>0.05), unlike carvedilol (-5.27 and -1.43 mm Hg, resp. p<0.05). Carvedilol and nebivolol increased of hypotension time index for diastolic BP in younger (7,6 and 7,7%, resp.) and elder (11 and 8,2% resp.) patients.Conclusion. Carvedilol in initial dose reduces systolic and pulse BP more significantly than nebivolol does in hypertensive elderly and senile patients. Increase of hypotension time index for diastolic BP revealed for both drugs can limit their use in patients with initially low diastolic BP.